QUALITY OF LIFE AND MENTAL HEALTH EDUCATION IN A RESIDENTIAL REHABILITATION SETTING IN ACEH, INDONESIA - Fathiariani, Liza; Mutia, Sunnia; Wati, Rahma; Fahdhienie, Farrah (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: In Indonesia, baseline data on quality of life (QoL) among rehabilitation residents are limited. This study aimed to assess the QoL of SUD residents at Rumoh Harapan Atjeh while providing a brief mental health education session. Methods: Nineteen male residents (18–60 years) undergoing rehabilitation for methamphetamine or cannabis use participated voluntarily. A 60-minute group education session was delivered, followed by completion of the WHOQOL-BREF (Bahasa Indonesia version) assessing physical, psychological, social, and environmental domains. Scores were transformed to a 0–100 scale and categorized as low (41–60), moderate (61–80), or high (>80). Ethical approval was not required, as the activity was categorized as community engagement without intervention. Informed consent and confidentiality were maintained. Results: Mean total QoL was 57.0 (low). Physical health scored highest (68.5, moderate), while psychological well-being (56.5), social relationships (58.5), and environment (54.5) remained low. All participants scored low in psychological and environmental domains, reflecting emotional distress and limited autonomy. Conclusion: Baseline QoL assessment identifies critical psychosocial needs among SUD residents. Integrating routine QoL monitoring and targeted psychosocial support into rehabilitation programs can enhance holistic recovery. Findings are preliminary due to the small sample size and single-site setting.